Faktor- Faktor yang Mempengaruhi Konsumsi Minyak Goreng Curah - zuraidah zuraidah; Gustami Harahap; Faoeza Hafiz Saragih (Jurnal Ilmiah Pertanian ( JIPERTA), 2019)
Cooking oil is one of the staple food consumed by all layers of society in Indonesia. At this time the cooking oil is sold in two forms, namely in bulk and packaged with certain brands/labels. Although branded cooking oil have many advantages and increasingly popular in the market city of Medan, but the demand  for cooking oil bulk is still higher compared to the branded cooking oil. The aim of the research was to analyse factors that affected consume bulk cooking oil demand in Deli Serdang district. This research is performed in traditional market in lubuk pakam. Sampling method technique is performed with aksidental (accidental sampling) that specifies the sample based on people who are found by chance or anyone who meets the criteria. the method sampling of this research use accedental sampling with 60 samples bulk cooking oil consumens. Variables of this research are the price of bulk cooking oil,income, family members and people’s taste.  Results of this is factors that affected the consume of Bulk cooking oil is the price of bulk cooking oil,otherwise Income , family members and taste do not affected in this research.